Potential, Prospect, and Investment Policy of Surabaya City - Sri Muljaningsih; Ignatia Martha Hendrati; Mohammad Wahed (Journal of Economics, Business, and Government Challenges, 2019)
This research aims to find out the types of superior investment potential that are the main attraction and the inhibiting factors and supporting the development of types of business or leading sectors. In this study using a quantitative approach with several stages of Location Quotient analysis tools, Shift Share, and Klassen Typology. The results of this study conclude that the economic structure of the city of Surabaya is dominated by 5 sectors, namely: a) the manufacturing industry sector; b) trade sector; c) the accommodation and food and beverage supply sector; d) information sector, and e) financial services sector. From the results of LQ which are included in the base category in Surabaya, including a) the electricity & gas procurement sector; b) water supply sector; c) the construction sector; d) trade sector; e) transportation sector; f) the accommodation supply sector; g) information; h) financial services sector; i) real estate sector; j) company service sector; k) the health service sector, and l) the health service sector. While the investment potential and opportunities in the city of Surabaya are based on the results of the analysis above then there are in the transportation sector, the accommodation supply sector, and the information sector.